Number theory vs. Hungarian high school textbooks: the fundamental theorem of arithmetic - Csányi, Petra; Fábián, Kata; Szabó, Csaba; Szabó, Zsanett (Teaching Mathematics and Computer Science, 2015)
We investigate how Hungarian highschool textbooks handle basic notions and terms of number theory. We concentrate on the presentation of the fundamental theorem of arithmetic, the least common multiple and greatest common divisor. Eight families of textbooks is analyzed. We made interviews with the authors of four of them. We conclude that a slightly more precise introduction would not be harmful for pupils and could bring basic number theory closer to them.